2003
DOI: 10.1159/000074648
|View full text |Cite
|
Sign up to set email alerts
|

The Supplementary Diagnostic Power of Selected Immunohistochemical, Molecular Genetic and Infective Parameters in Epithelial Hyperplastic Laryngeal Lesions

Abstract: Objectives: MIB-1 and p53 protein expression, loss of heterozygosity (LOH), microsatellite instability (MSI) of di- and mononucleotide repeats, and HPV status were tested for their potential to characterize different stages of epithelial hyperplastic laryngeal lesions (EHLL). Methods: Thirty-two EHLL were reclassified according to the Ljubljana classification into simple (SH), abnormal (AbH), atypical hyperplasia (AtH) and carcinoma in situ, and investigated by immunohistochemical methods, PCR and direct seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In general, our study revealed a high rate of allelic alterations in loci around 3p21-14 and 9p22-21 without divergent results for the loci which were included in our previous study [12]. The chromosomal arms 3p and 9p have already been found to be early and frequently altered in oral and laryngeal hyperplastic and premalignant lesions of previous studies [8, 17].…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…In general, our study revealed a high rate of allelic alterations in loci around 3p21-14 and 9p22-21 without divergent results for the loci which were included in our previous study [12]. The chromosomal arms 3p and 9p have already been found to be early and frequently altered in oral and laryngeal hyperplastic and premalignant lesions of previous studies [8, 17].…”
Section: Discussionsupporting
confidence: 55%
“…Of those, 27 specimens have been presented in a recent study [12]. The median age at laryngoscopy was 60.5 years (range 44–80).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations